Regenerative medicine and carboxytherapy: a promising combination for androgenetic alopecia - Amore, Antonio Luca; Bartoletti, Emanuele; Gennai, Alessandro (Aesthetic Medicine, 2024)
Background: Androgenetic alopecia, a disease that affects 70% of men and 40% of women, is characterized by the gradual miniaturization of the hair follicle, resulting from the alteration of the dynamics of the hair cycle. Aim: One of the most recent and promising advanced medical therapies is regenerative medicine. The important action of Adipose Derived Stem Cells (ADSCs) on the hair follicle is that of inducing anagen by stimulating the stem cells of the hair follicle. The Fibroblastic growth factor expressed by ADSCs also plays an important role in regulating the bulge and in the basal layer of the epidermis, inducing follicular neogenesis. In association with regenerative therapy, carboxytherapy was used with its neoangiogenic potential, exerts its synergistic action. Methods: This study aims to evaluate the effectiveness of the technique used for the therapy of androgenetic alopecia. The protocol involved the association of carboxytherapy and regenerative therapy through the grafting of vascular stromal fraction and mesenchymal stem cells of adipose origin. Through trichoscopic images and the use of innovative software, the data relating to the clinical variations of the pathology examined were extrapolated and subsequently statistically analysed. Results: 10 patients were enrolled (6 men and 4 women). To evaluate the clinical evolution of the pathology in question, both the clinical scales (Norwood in men and Ludwig in women) and the data extrapolated from the trichoscopic images relating to the ratio between the number of terminal hairs present for each vellus hair (PT/PV) were considered. The variation proved to be statistically significant both by analyzing the average of all areas (P = 0.0018) and by analyzing the areas with the best and worst ratios (P = 0.0032 and P = 0.0106 respectively). Conclusions: In consideration of the significance of the data obtained, this study demonstrates once again how the association of regenerative therapy and carboxytherapy is an optimal combination in the treatment of androgenetic alopecia.